A Multicenter Evaluation of a Point-of-Care Blood Glucose Meter System in Critically Ill Patients. (5th June 2021) - Nichols, James H; Brandler, Ethan S; Fantz, Corinne R; Fisher, Kimberley; Goodman, Michael D; Headden, Gary; Hoppensteadt, Debra; Matika, Ryan; Peacock, W Frank; Rodrigo, John; Schützenmeister, Andre; Swanson, Jonathan R; et al.
Abstract: Background: Our purpose was to evaluate the performance of the ACCU-CHEK ® Inform II blood glucose monitoring system (Roche Diagnostics GmbH) compared with the perchloric acid hexokinase (PCA-HK) comparator method on the cobas ® 6000 analyzer (Roche Diagnostics International Ltd) in critically ill patients. Methods: Overall, 476 arterial (376 pediatric/adult, 100 neonate), 375 venous, and 100 neonatal heel-stick whole-blood samples were collected and evaluated from critical care settings at 10 US hospitals, including the emergency department, medical and surgical intensive care units (ICUs), and neonatal and pediatric ICUs. The ACCU-CHEK Inform II system was evaluated at 2 cutoff boundaries: boundary 1 was ≥95% of results within ±12 mg/dL of the reference (samples with blood glucose <75 mg/dL) or ±12% of the reference (glucose ≥75 mg/dL), and boundary 2 was ≥98% of results within ±15 mg/dL or ±15% of the reference. Clinical performance was assessed by evaluating sample data using Parkes error grid, Monte Carlo simulation, and sensitivity and specificity analyses to estimate clinical accuracy and implications for insulin dosing when using the ACCU-CHEK Inform II system. Results: Proportions of results within evaluation boundaries 1 and 2, respectively, were 96% and 98% for venous samples, 94% and 97% for pediatric and adult arterial samples, 84% and 98% for neonatal arterial samples, and 96% and 100% for neonatal heel-stick samples. Clinical evaluation demonstrated high specificity and sensitivity, with low risk of potential insulin-dosing errors. Conclusions: The ACCU-CHEK Inform II system demonstrated clinically acceptable performance against the PCA-HK reference method for blood glucose monitoring in a diverse population of critically ill patients in US care settings.